2019
DOI: 10.1186/s13011-019-0203-8
|View full text |Cite
|
Sign up to set email alerts
|

High levels of alcohol intoxication and strong support for restrictive alcohol policies among music festival visitors

Abstract: Background Alcohol intoxication is associated with problems such as violence, injuries, drunk driving and sexual risk-taking, and music festivals are considered a high-risk setting for high levels of alcohol consumption. This study investigates intoxication levels, drinking habits, and opinions on alcohol use and alcohol policies among visitors at one of the largest music festivals in Sweden in 2017. Methods A cross-sectional study assessing alcohol intoxication levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 53 publications
0
9
0
1
Order By: Relevance
“…Thus, there is room for improvement with regards to compliance to the Alcohol Act, which states that alcohol is not to be served to obviously intoxicated patrons. We have previously shown that every third visitor at the same festival was heavily intoxicated [ 1 ], similar to a festival in Norway [ 2 ]. Overserving at licensed premises at the festival is one factor that contributes to the overall high intoxication level among visitors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, there is room for improvement with regards to compliance to the Alcohol Act, which states that alcohol is not to be served to obviously intoxicated patrons. We have previously shown that every third visitor at the same festival was heavily intoxicated [ 1 ], similar to a festival in Norway [ 2 ]. Overserving at licensed premises at the festival is one factor that contributes to the overall high intoxication level among visitors.…”
Section: Discussionmentioning
confidence: 99%
“…Music festivals are events where several thousands of people, mainly young, gather and socialize, often over several days, and alcohol is usually a focal point that contributes to the festival experience. High levels of alcohol intoxication among festival-goers [ 1 , 2 , 3 ] and risky consumption [ 4 , 5 , 6 ] are concerning, since alcohol increases the risk for a number of public health-related problems such as injuries, sexual harassment, and violence [ 7 , 8 , 9 ], especially in large crowds [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limitation of the study is the substantial internal drop-out regarding questions of main setting of use and consequences of drug use. Moreover, 72% of the respondents were male, which might reflect a selection bias, as indicated by the following studies: (1) offline studies at one large festival and a large EDM event in Sweden consisted of 64 percent males in each study [ 18 , 81 ]; (2) a comparison of online and offline recruitment in the remaining European countries of the ALAMA study indicates that the online and offline sample consisted of 69% and 58% males, respectively [ 82 ]. Furthermore, the online participants were on average one year younger compared with offline participants, and drug use was slightly less prevalent in the online sample [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Sweden, the legal limit for DUI is 0.020%, and the limit for gross DUI is 0.100%. Therefore, studies conducted in Sweden commonly use a threshold of 0.100% (Durbeej, Elgan, Jalling, & Gripenberg, 2017; Feltmann, Elgan, & Gripenberg, 2019; Gripenberg-Abdon et al, 2012). Studies measuring actual intoxication levels among university students are relatively rare, particularly in the Swedish context.…”
mentioning
confidence: 99%